2013
DOI: 10.1093/brain/awt308
|View full text |Cite
|
Sign up to set email alerts
|

Sustained peripheral depletion of amyloid-β with a novel form of neprilysin does not affect central levels of amyloid-β

Abstract: Lowering levels of peripheral amyloid-β has been proposed as a strategy to reduce plaques in patients with Alzheimer’s disease. Henderson et al. test a modified version of the amyloid-degrading enzyme neprilysin in rats, monkeys and Tg2576 mice. Levels of amyloid-β were reduced in the bloodstream, but not in the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 43 publications
5
49
0
1
Order By: Relevance
“…For example, it has been suggested that cerebral Ab accumulation may be partly a downstream consequence of age or vascular diseaseerelated microvascular injury (Sagare et al, 2013). Alternative theories have also been substantiated by studies demonstrating differential impact of anti-Ab antibodies on Ab levels in the blood and peripheral blood suggesting that soluble AB may need to be depleted within the central nervous system instead of the peripheral blood system (Georgievska et al, 2014;Henderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that cerebral Ab accumulation may be partly a downstream consequence of age or vascular diseaseerelated microvascular injury (Sagare et al, 2013). Alternative theories have also been substantiated by studies demonstrating differential impact of anti-Ab antibodies on Ab levels in the blood and peripheral blood suggesting that soluble AB may need to be depleted within the central nervous system instead of the peripheral blood system (Georgievska et al, 2014;Henderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whereas Ab production necessarily occurs exclusively in the proximity of b-and c-secretase, Ab degradation can take place any arbitrary distance from the sites of Ab production [56]. Indeed, some reports have suggested that increasing Ab degradation (or sequestration [63]) in the periphery can lower cerebral Ab levels [64,65], although these initial results were not confirmed in several well-designed studies [66,67]. Nevertheless, from a drug-development perspective, the fact that AbDP-targeting therapies can operate at some distance from the source of Ab production represents a distinct advantage over existing Ab-lowering strategies.…”
Section: General Features Of Abdpsmentioning
confidence: 97%
“…The brain neprilysin has been shown to play a key role in degrading β‐amyloid, of which aggregation into plaques is one of the hallmarks of AD 120. It is not likely that peripheral inhibition of neprilysin affected brain β‐amyloid levels by inhibiting the peripheral sink effect, which is suggested as an alternative for β‐amyloid removal 121, 122. However, if LCZ696 was to penetrate the blood–brain barrier, it could, in theory, accelerate the progression of AD by reducing β‐amyloid degradation in brain.…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%